High‐Performance Lithium–Oxygen Batteries Using a Urea‐Based Electrolyte with Kinetically Favorable One‐Electron Li2O2 Oxidation Pathways. (26th July 2022) - Sun, Zongqiang; Lin, Xiaodong; Wang, Chutao; Hu, Ajuan; Hou, Qing; Tan, Yanyan; Dou, Wenjie; Yuan, Ruming; Zheng, Mingsen; Dong, Quanfeng
Abstract: Glymes are the most widely used electrolyte solvents in lithium–oxygen batteries (LOBs) due to their relatively high stability. However, their associated LOBs have long been plagued by large charge overpotential, which is closely related to the sluggish two‐electron Li2 O2 oxidation mechanism. Here, we report a new electrolyte solvent—1, 1, 3, 3‐tetramethylurea (TMU) for LOBs with high performance and an alternative mechanism, where a kinetically favorable one‐electron Li2 O2 oxidation pathway can happen in the urea electrolyte system, thus leading to a much lower charge overpotential (≈0.51 V) compared to the tetraglyme‐based LOBs (≈1.27 V). Besides, TMU also exhibits good stability since it does not contain any α‐hydrogen atoms that are vulnerable to be attacked by superoxide species, thus suppressing the hydrogen abstraction side reactions. Consequently, the TMU‐based LOBs can stably work for more than 135 cycles, which is four times that of the tetraglyme‐based LOBs (≈28 cycles). Abstract : A new electrolyte solvent—1, 1, 3, 3‐tetramethylurea (TMU) is proposed for lithium–oxygen batteries (LOBs). Benefiting from its strong Li + ‐solvating ability and the absence of α‐hydrogen atoms, a kinetically favorable one‐electron Li2 O2 oxidation pathway can occur in the charge process, and the hydrogen extraction side reactions can be effectively suppressed. Consequently, the TMU‐based LOBs exhibit a low charge overpotential and a long cycle life.